60 DE ANI AI STUDIOULUI „MOLDOVA-FILM”: (Evoluţia filmului documentar în istoriografia moldovenească) - MOLDOVANU, bibliotecar principal, Filiala de Arte „Tudor Arghezi”, Anastasia (BIBLIOPOLIS, 2020)
The film studio Moldova-film accomplished 60 years. The activity of this institution is described for ones as an colossus, and others are waiting for full flourish of the national cinematography and legislation changes related to the existence and function of this organism. The studio Moldova fi lm was conceived as a Chronic and Documentary film studio. In the 50s when the Soviet cinematography was seeking new ways for artistic expression, art film in Moldova began to expand the range of its activity. The researches on national cinema demonstrate that the Moldovan fi lm, although developed on the Russian school of cinematography, in practice was based on the local film. The films created over the years: Hajduk ballad (Baladă haiducească), Fiddlers (Lăutarii), Is seeking a security guard (Se caută un paznic), Last fall month (Ultima lună de toamnă), Wait for us at dawn (Aşteptaţi-ne în zori), When the cranes go (Când se duc cocorii), Taste bread (Gustul pâinii), Red Meadows (Poienile roşii) – became symbols of value created by Moldovan fi lmmakers A. Plamadeala, E. Loteanu, V. Dude, V. Pascaru; operators V. Ciurea, V. Calaşnicov, P. Balan, I. Bolboceanu, I. Drill, V. Brescanu. In recent years, at the intersection of the century, a serious issue, migration, was the subject of the documentary film. The national cinematography, built and cemented within a century of tradition, is now accumulating forces with new creative potential which may exceed critical situations.